2019
DOI: 10.3390/atmos10090483
|View full text |Cite
|
Sign up to set email alerts
|

Response of Urban Heat Stress to Heat Waves in Athens (1960–2017)

Abstract: The increasing frequency, intensity and duration of heat waves seem to follow the observed global warming in recent decades. Vulnerability to heat waves is expected to increase in urban environments mainly due to population density and the effect of the urban heat island that make cities hotter than surrounding non-urban areas. The present study focuses on a vulnerable area of the eastern Mediterranean, already characterized as a ‘hot spot’ with respect to heat-related risk and investigates the change in heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 71 publications
4
14
0
Order By: Relevance
“…Similar results were found in New York City (135). In Athens, Greece, trends in nocturnal heat stress conditions during heat waves also increase more in urban than rural environments (139) but are comparable during the day. Depietri & McPhearson (135) showed that for New York City impacts on mortality and morbidity decrease despite the increase in heat waves, probably due to an adaptation of warning systems and the development of air-conditioning.…”
Section: Learning From Past Trends and Eventssupporting
confidence: 81%
“…Similar results were found in New York City (135). In Athens, Greece, trends in nocturnal heat stress conditions during heat waves also increase more in urban than rural environments (139) but are comparable during the day. Depietri & McPhearson (135) showed that for New York City impacts on mortality and morbidity decrease despite the increase in heat waves, probably due to an adaptation of warning systems and the development of air-conditioning.…”
Section: Learning From Past Trends and Eventssupporting
confidence: 81%
“…UHI has enormous direct and indirect impacts on urban regions and dwellers, such as causing a considerable rise in energy consumption for cooling purposes [4,[14][15][16] and increasing heat-related mortality and morbidity, especially for vulnerable groups such as senior and low-income citizens [4,9,[17][18][19][20]. These impacts are reported to be intensified during heatwave (HW) events, a period of excessively hot days [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Napoli et al have assessed the thermal bioclimate of Europe for the summer season and concluded that an increase in heat stress up to 1 • C was observed from 1979 to 2016 [27]. Some scholars pointed out that southern Europe (Crete Island in Greece, Eastern Mediterranean, Athens, Madrid (Spain), Novi Sad (Vojvodina, Northern Serbia)) were under high temperature and pressure, and climate warming has led to a significant increase in the frequency and duration of high-temperature heat waves in southern Europe and a decline in climate comfort [28][29][30][31][32][33][34][35]. In central Europe, climate change has led to an increase in the number of strong and very strong heat stress days in Poland [36].…”
Section: Introductionmentioning
confidence: 99%